Moving to Higher Ground: Migration Response to Natural Disasters in the Early Twentieth Century - Boustan, Leah Platt; Kahn, Matthew E; Rhode, Paul W (American Economic Review, 2012)
Areas differ in their propensity to experience natural disasters. Exposure to disaster risks can be reduced either through migration (i.e., self-protection) or through public infrastructure investment (e.g., building seawalls). Using migration data from the 1920s and 1930s, this paper studies how the population responded to disaster shocks in an era of minimal public investment. We find that, on net, young men move away from areas hit by tornados but are attracted to areas experiencing floods. Early efforts to protect against future flooding, especially during the New Deal era of the late 1930s, may have counteracted an individual migration response.